Artificial Rainfall Aquifer to Supply Clean Water Requirement During the Dry Season in Selengen Village, North Lombok Regency - I Wayan Yasa; Didi Supriyadi Agustawijaya; Atas Pracoyo; Ery Setiawan; Hasyim Hasyim; I Dewa Made Alit Karyawan; Humairoh Saidah; I Dewa Gede Jayanegara; Dewandha Mas Agastya (Pascasarjana Universitas Mataram, 2024)
Selengen Village is one of the villages in North Lombok Regency that always experiences drought and lack of clean water every year. The problem of clean water availability is caused by limited water sources on the surface. The frequency of rainwater in Selengen Village is very small and with very low intensity. In order to meet the need for clean water, the community has to pay additional costs to buy clean water or wait for a drop from the government. The Selengan Village community has limited information regarding simple methods that can be used to collect clean water sourced from rainwater. The method used to introduce rainwater capture as a source of clean water is to provide direct outreach to the Selengen Village community about rainwater storage in the form of ABSAH (Artificial Aquifer for Rainwater Savings). The ABSAH method can be done individually or in groups. The socialization was carried out at the Panggung Barat Hamlet office involving the community consisting of farmer groups, community leaders, youth organizations and housewives. The result of the socialization regarding the introduction of artificial rainwater aquifers is the high desire of the community to create rainwater storage, either independently/individually or in groups. In the process of making it, the community hopes to get assistance from the implementation team so that the calculation of the storage volume is in accordance with the volume of water used. Apart from that, the community also hopes to be given drawings of storage designs, installations for collecting water from the roofs of houses and designs of distribution networks to people's homes.